Attachment and motivational systems: Relevance of sensitivity to punishment for eating disorder psychopathology. (February 2018) - Monteleone, Alessio Maria; Cardi, Valentina; Volpe, Umberto; Fico, Giovanna; Ruzzi, Valeria; Pellegrino, Francesca; Castellini, Giovanni; Monteleone, Palmiero; Maj, Mario
Abstract: An altered balance of reward and inhibition systems may explain Eating Disorder (ED) behaviors and could be related to difficulties in socio-emotional processing. According to attachment theory, early interaction with caregivers affects the ability to regulate emotion in adult interpersonal situation. The aim of our study was to investigate if insecure attachment may be related to ED symptomatology through changes in reward and inhibition systems. Seventy-eight people affected by EDs and 45 healthy controls (HC) filled in the Attachment Style Questionnaire (ASQ), the Behavioral Inhibition System-Behavioral Activation System Scale (BIS-BAS) and the Eating Disorders Inventory-2 (EDI-2) questionnaire. ED people reported significantly higher scores than HC in EDI-2 scores, all dimensions of insecure attachment style and sensitivity to punishment (BIS score). In ED patients, ASQ anxiety scores correlated with almost all EDI-2 subscores and sensitivity to punishment. The association between anxious attachment style and ED symptomatology (drive to thinness and body dissatisfaction) was totally mediated by an indirect effect of sensitivity to punishment. These findings suggest, for the first time, increased sensitivity to punishment as a pathway that may explain the relationship between anxious attachment and ED symptomatology highlighting the relevance to target social experiences as an important psychotherapeutic focus. Highlights: ED people showed high levels of insecure attachment and punishment sensitivity. Insecure attachment and sensitivity to punishment correlated with ED symptomatology. Sensitivity to punishment mediated the effects of anxious attachment on ED psychopathology. Social experiences are an important focus in psychotherapeutic interventions.